Analisis Faktor-Faktor Yang Memengaruhi Kualitas Pelayanan Dokter Program Pendidikan Dokter Spesialis 1 Terhadap Kepuasan Pegawai - William T. Palandeng; B.H. Ralph Kairupan; Billy J. Kepel; Aaltje E. Manampiring; E. David Kaunang (Journals of Ners Community, 2023)
The teaching hospital has medical personnel participating in the Specialist Doctor Education Program 1 (PPDS-1) known as resident doctors. The management of the Specialist Doctor Education Program 1 is closely related to health services in teaching hospitals. Every PPDS-1 doctor must have good health care quality dimensions including reliability, responsiveness, assurance, attention, and appearance. Evaluation of fellow health professionals will provide a more objective assessment, especially in evaluating the process of services provided by PPDS-1 doctors in hospitals. This study aims to explain the influence of factors related to the quality of PPDS-1 doctor services including; reliability, responsiveness, assurance, attention, and appearance to the satisfaction of RSUP employees Prof. Dr. R. D. Kandou Manado. This research design is an analytical survey research with a cross sectional approach. The population in this study was employees of RSUP Prof. Dr. R. D. Kandou Manado who were in the patient care room amounting to 1,704 people. The sampling technique is probability sampling and the sample is taken by stratified sampling technique, with a sample size according to Slovin 324 health workers. The research instrument used questionnaires. Data were analyzed using SPSS program univariately, bivariate using Chi Square test, and multivariate analysis using logistic regression test. Based on the results of the study, it can be concluded that factors related to the quality of PPDS-1 doctor services include; Reliability, responsiveness, assurance, attention, and appearance affect the satisfaction of RSUP employees Prof. Dr. R. D. Kandou Manado, where the responsiveness factor has the greatest influence on the satisfaction of RSUP employees Prof. Dr. R. D. Kandou Manado.